Anatomical and molecular imaging of skin cancer - Hao Hong; Jiangtao Sun; Weibo Cai (Dove Medical Press, 2008)
Hao Hong1, Jiangtao Sun1, Weibo Cai1,21Departments of Radiology and Medical Physics, School of Medicine and Public Health, University of Wisconsin – Madison, Madison, Wisconsin, USA; 2University of Wisconsin Paul P. Carbone Comprehensive Cancer Center, Madison, Wisconsin, USAAbstract: Skin cancer is the most common form of cancer types. It is generally divided into two categories: melanoma (∼5%) and nonmelanoma (∼95%), which can be further categorized into basal cell carcinoma, squamous cell carcinoma, and some rare skin cancer types. Biopsy is still the gold standard for skin cancer evaluation in the clinic. Various anatomical imaging techniques have been used to evaluate different types of skin cancer lesions, including laser scanning confocal microscopy, optical coherence tomography, high-frequency ultrasound, terahertz pulsed imaging, magnetic resonance imaging, and some other recently developed techniques such as photoacoustic microscopy. However, anatomical imaging alone may not be sufficient in guiding skin cancer diagnosis and therapy. Over the last decade, various molecular imaging techniques (in particular single photon emission computed tomography and positron emission tomography) have been investigated for skin cancer imaging. The pathways or molecular targets that have been studied include glucose metabolism, integrin αvβ3, melanocortin-1 receptor, high molecular weight melanoma-associated antigen, and several other molecular markers. Preclinical molecular imaging is thriving all over the world, while clinical molecular imaging has not lived up to the expectations because of slow bench-to-bedside translation. It is likely that this situation will change in the near future and molecular imaging will truly play an important role in personalized medicine of melanoma patients.Keywords: skin cancer, molecular imaging, melanoma, anatomical imaging, positron emission tomography, antibody